Women as Subalterns: An Analysis of Khaled Hosseini's Novel The Kite Runner - Surendra Prasad Ghimire (Journal of Language and Literature, 2023)
This research article reports how Hosseini's novel The Kite Runner depicted subaltern women characters and their consciousness regarding the injustices imposed on them. There have been a limited number of female characters in the novel, albeit they have been enough to explore the ground reality of their contemporary time. This study utilized subaltern theories, particularly those developed by Ranajit Guha and Gayatri Chakravorty Spivak, to explore the depiction and consciousness of subaltern women characters in the novel. The findings of this article reveal that the majority of the women characters were victimized and ignored in society because of their socio-cultural stereotypes and national and international intervention in their lives. As a result, they were deprived of the opportunity to follow their passions and make their own decisions, not only in their society but also within their families. This study further shows how social, cultural, and religious milieus became responsible for making them invisible and unheard in their own society. In addition, this study sheds light on how patriarchal ideology became an indispensable component of women's marginalization by restricting their voices, freedom, and social mobility. However, the majority of the female characters developed their consciousness about injustices against them and resisted such injustices by breaching long-established social and religious norms and values in their society. In a broader sense, this study will have important significance in unfolding subaltern women's ground reality in further study.